Interaksi Sarjana Muslim dan Sarjana Barat dalam Diskursus Hadis - M Khusnun Niam (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2020)
Hadith is everything that is based on the Prophet Muhammad Salallahu Alaihi Wassalam, both in the form of words, attitudes, and other cases in which there is approval of the Prophet Muhammad Salallahu Alaihi Wassalam. His position became the second source of law after the Qur'an because it contained news that could be used as a guide by Muslims. The development of hadith is not like the Qur'an which is easy and smooth. This is due to the large number of Western scholars who began to weaken Islam by studying the hadith to find evidence of the authenticity of the hadith. So that the hadith experts try to put up a fight by exposing the error of the study of Western scholars related to the hadith discourse. This article aims to describe the various discourses on hadith, both from among Muslims and non-Islamic circles or Orientalists. The aim is none other than trying to find views on the traditions of Muslim scholars and among Western scholars who study the hadith. In addition, as for the specific purpose is to find the interaction that occurs from the Muslim community over their views on the Orientalist